Application of ASR tests to recycled concrete aggregates: Influence of water absorption. (15th October 2016) - Delobel, F.; Bulteel, D.; Mechling, J.M.; Lecomte, A.; Cyr, M.; Rémond, S.
Highlights: Water absorption has to be considered for the manufacture of samples for ASR tests. New procedure is proposed to determine WA24 of fine fraction used in microbar tests. Tested RCA present expansions larger than standard thresholds defined for ASR. Abstract: Concrete is one of the most abundant construction and demolition wastes. It can be crushed to produce Recycled Concrete Aggregates (RCA) that can eventually be recycled for the manufacture of new concrete. However, the presence of adherent cement paste leads to higher alkalis content in these aggregates that could increase the risk to observe Alkali Silica Reaction (ASR). Moreover, the origin of natural aggregates in the RCA is generally unknown and these aggregates can potentially be reactive concerning ASR. Among standards which qualify the risk of ASR for natural aggregates, two main tests are used in this paper to evaluate the risk of ASR of RCA: tests on mortars and tests on microbars. In these tests, the water absorption of aggregates is not taken into consideration for the effective water calculation. However, in the case of absorbing aggregates like RCA, absorption water cannot be neglected. It could change significantly the effective water to cement ratio, and then influence the measured expansion. The first aim of this paper is to study the influences of absorption water and initial saturation state of RCA on the expansion of mortars and microbars. The second objective is to propose a new simple method for the assessment of water absorption coefficient of the fine granular fraction 0.16/0.63 mm used for the manufacture of microbars. It is shown that absorption water has a strong influence on the expansion of mortars and microbars made with RCA, and that it has to be taken into account in the composition of the mixes. The initial state of saturation of RCA is less influential. The proposed method for the water absorption coefficient determination of fraction 0.16/0.63 mm is based on the correlation between water absorption and cement paste content. The estimation of the latter from the mass loss between 105 and 475 °C for two fractions of RCA, allows for an accurate determination of the water absorption coefficient of the fine fraction.